Un año sin domingos : la imagen de la alfabetización en Cuba = A year without Sundays : images from the literacy campaign in Cuba - Murphy, Catherine; Torres Cairo, Carlos (Aurelia Ediciones ; The Literacy Project, 2018)
"Cuba, 1961. Thousands of young men and women join the National Campaign for Literacy. This compilation of testimonies and images tell the lived experiences of a year that changed lives. A year without Sundays, dedicated to teaching others how to read and write."--Publisher's description.